Synthesis and electrical characterization of intrinsic and in situ doped Si nanowires using a novel precursor - Molnar, Wolfgang; Lugstein, Alois; Wojcik, Tomasz; Pongratz, Peter; Auner, Norbert; Bauch, Christian; Bertagnolli, Emmerich (Beilstein Journal of Nanotechnology, 2012)
Perchlorinated polysilanes were synthesized by polymerization of tetrachlorosilane under cold plasma conditions with hydrogen as a reducing agent. Subsequent selective cleavage of the resulting polymer yielded oligochlorosilanes SinCl2n+2 (n = 2, 3) from which the octachlorotrisilane (n = 3, Cl8Si3, OCTS) was used as a novel precursor for the synthesis of single-crystalline Si nanowires (NW) by the well-established vapor–liquid–solid (VLS) mechanism. By adding doping agents, specifically BBr3 and PCl3, we achieved highly p- and n-type doped Si-NWs by means of atmospheric-pressure chemical vapor deposition (APCVD). These as grown NWs were investigated by means of scanning electron microscopy (SEM) and transmission electron microscopy (TEM), as well as electrical measurements of the NWs integrated in four-terminal and back-gated MOSFET modules. The intrinsic NWs appeared to be highly crystalline, with a preferred growth direction of [111] and a specific resistivity of ρ = 6 kΩ·cm. The doped NWs appeared to be [112] oriented with a specific resistivity of ρ = 198 mΩ·cm for p-type Si-NWs and ρ = 2.7 mΩ·cm for n-doped Si-NWs, revealing excellent dopant activation.
Keywords: chemical vapour deposition; field-effect transistor; oligosilanes; radiation-induced nanostructures; silicon nanowires; vapor–liquid–solid mechanism

(untitled) - Duan, X.; Huang, Y.; Lieber, C. M. (Nano Lett., 2002)

(untitled) - Javey, A.; Nam, S.; Friedman, R. S.; Yan, H.; Lieber, C. M. (Nano Lett., 2007)

(untitled) - Cui, Y.; Lieber, C. M. (Science, 2001)

(untitled) - Zheng, G.; Patolsky, F.; Cui, Y.; Wang, W. U.; Lieber, C. M. (Nat. Biotechnol., 2005)

(untitled) - Pettersson, H.; Trägårdh, J.; Persson, A. I.; Landin, L.; Hessman, D.; Samuelson, L. (Nano Lett., 2006)

(untitled) - Martel, R.; Derycke, V.; Lavoie, C.; Appenzeller, J.; Chan, K. K.; Tersoff, J.; Avouris, P. (Phys. Rev. Lett., 2001)

(untitled) - Duan, X.; Huang, Y.; Cui, Y.; Wang, J.; Lieber, C. M. (Nature, 2001)

(untitled) - Brus, L. (J. Phys. Chem., 1994)

(untitled) - Yorikawa, H.; Uchida, H.; Muramatsu, S. (J. Appl. Phys., 1996)

(untitled) - Mozos, J. L.; Machado, E.; Hernandez, E.; Ordejon, P. (Int. J. Nanotechnol., 2005)

(untitled) - Wagner, R. S.; Ellis, W. C. (Appl. Phys. Lett., 1964)

(untitled) - Arakawa, Y. (Solid-State Electron., 1994)

(untitled) - Martelli, F.; Piccin, M.; Bais, G.; Jabeen, F.; Ambrosini, S.; Rubini, S.; Franciosi, A. (Nanotechnology, 2007)

(untitled) - Wang, N.; Tang, Y. H.; Zhang, Y. F.; Lee, C. S.; Lee, S. T. (Phys. Rev. B, 1998)

Whisker Technology - Levitt, A. P. (Wiley-Interscience, 1970)

(untitled) - Givargizov, E. I. (J. Cryst. Growth, 1975)

(untitled) - Lugstein, A.; Hyun, Y. J.; Steinmair, M.; Dielacher, B.; Hauer, G.; Bertagnolli, E. (Nanotechnology, 2008)

(untitled) - Sharma, S.; Kamins, T. I.; Stanley Williams, R. (J. Cryst. Growth, 2004)

(untitled) - Iacopi, F.; Vereecken, P. M.; Schaekers, M.; Caymax, M.; Moelans, N.; Blanpain, B.; Richard, O.; Detavernier, C.; Griffiths, H. (Nanotechnology, 2007)

(untitled) - Björk, M. T.; Knoch, J.; Schmidt, H.; Riel, H.; Riess, W. (Appl. Phys. Lett., 2008)

(untitled) - Sharma, S.; Sunkara, M. K. (Nanotechnology, 2004)

(untitled) - Schmidt, V.; Riel, H.; Senz, S.; Karg, S.; Riess, W.; Gösele, U. (Small, 2006)

(untitled) - Lew, K.-K.; Pan, L.; Bogart, T. E.; Dilts, S. M.; Dickey, E. C.; Redwing, J. M.; Wang, Y.; Cabassi, M.; Mayer, T. S.; Novak, S. W. (Appl. Phys. Lett., 2004)

(untitled) - Schmid, H.; Björk, M. T.; Knoch, J.; Karg, S.; Riel, H.; Riess, W. (Nano Lett., 2009)

(untitled) - Xie, P.; Hu, Y.; Fang, Y.; Huang, J.; Lieber, C. M. (Proc. Natl. Acad. Sci. U. S. A., 2009)

(untitled) - Molnar, W.; Lugstein, A.; Pongratz, P.; Auner, N.; Bauch, C.; Bertagnolli, E. (Nano Lett., 2010)

Einführung in das anorganisch-chemische Praktikum - Jander, G.; Blasius, E. (S. Hirtzel Verlag, 1995)

(untitled) - Schmeisser, M.; Voss, P. (Z. Anorg. Allg. Chem., 1964)

(untitled) - Sharp, K. G.; Sutor, P. A.; Williams, E. A.; Cargioli, J. D.; Farrar, T. C.; Ishibitsu, K. (J. Am. Chem. Soc., 1976)

(untitled) - Marsmann, H. C.; Raml, W.; Hengge, E. (Z. Naturforsch., 1980)

(untitled) - Briand, D.; Sarret, M.; Kis-Sion, K.; Mohammed-Brahim, T.; Duverneuil, P. (Semicond. Sci. Technol., 1999)

(untitled) - Lugstein, A.; Andrews, A. M.; Steinmair, M.; Hyun, Y.-J.; Bertagnolli, E.; Weil, M.; Pongratz, P.; Schramböck, M.; Roch, T.; Strasser, G. (Nanotechnology, 2007)

(untitled) - Lauhon, L. J.; Gudiksen, M. S.; Wang, D.; Lieber, C. M. (Nature, 2002)

(untitled) - Yu, J.-Y.; Chung, S.-W.; Heath, J. R. (J. Phys. Chem. B, 2000)

(untitled) - Zhang, S.; Hemesath, E. R.; Perea, D. E.; Wijaya, E.; Lensch-Falk, J. L.; Lauhon, L. J. (Nano Lett., 2009)

(untitled) - Sarkar, J.; Khan, G. G.; Basumallick, A. (Bull. Mater. Sci., 2007)